The Physical and Mental Health of Off-Reserve First Nations Children of Teen Mothers - Guèvremont, Anne; Kohen, Dafna (International Indigenous Policy Journal, 2013)
The teen birth rate for First Nations women is higher than the teen birth rate for non-Aboriginal women. While associations between physical and behavioural outcomes have been examined in non-Aboriginal children with teen mothers, fewer studies have focused on First Nations children of teen mothers. This study uses data from the 2006 Aboriginal Children’s Survey to compare physical and mental health outcomes of 2- to 5-year-old off-reserve First Nations children of teenage and older mothers. There were few differences in physical health outcomes between off-reserve First Nations children of teen mothers and older mothers with the exception of dental health. However, for all of the mental health outcomes examined, child prosocial behaviours, emotional symptoms, inattention-hyperactivity, and conduct problems, scores were poorer for off-reserve First Nations children of teen mothers. Although the differences in prosocial and emotional problems were attributable to socio-economic factors, differences in child inattention-hyperactivity and conduct problems were not. Future research would help our understanding of the differences in outcomes between off-reserve First Nations children of teen and older mothers.